PENGARUH PENDIDIKAN, KEMISKINAN DAN KETIMPANGAN TERHADAP PENDAPATAN MASYARAKAT KABUPATEN LANGKAT SUMATERA UTARA - MUHAMMAD ARFAN HARAHAP; AHMAD DAUD (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to see the level of significance of the influence of Education, Poverty and Inequality Towards Community Income in Langkat District of North Sumatra, both partially and simultaneously. This research is a quantitative study, using secondary data obtained from the Central Statistics Agency (BPS). The population of this study consists of the total number of people who have never taken education, the percentage of poverty level and the level of inequality / Gini Ratio as well as the total income of the community / GRDP of Langkat Regency, North Sumatra Province. The sample starts from 2010 until 2019 with annual data. This research model uses multiple linear regression models with a significance level of 5%. Research data were processed using the SPSS 25 program. The classic assumption test results are that the research data is stated to be normally distributed, free from deviations from classical assumptions (multi-colinearity, auto correlation, hetero scedasticity) and independent variables (Education, Poverty Level and Life Inequality able to explain the dependent variable (Community Income) of 92.8 Partially, the Education variable has a very significant negative effect on Community Income and the Inequality variable has a very significant negative effect on Community Income while the Poverty Level variable has a Significant effect on Community Income